Respuesta :

Answer:

11)  [tex]y=-(x-6)^2+4[/tex]

12)  [tex]y=(x+5)^2[/tex]

Step-by-step explanation:

Vertex form of a parabola:  

[tex]y=a(x-h)^2+k[/tex]  where (h, k) is the vertex

Question 11

From inspection of the graph, the vertex is (6, 4)

[tex]\implies y=a(x-6)^2+4[/tex]

To find [tex]a[/tex], substitute the coordinates of a point on the curve into the equation.

Using point (4, 0):

[tex]\implies a(4-6)^2+4=0[/tex]

[tex]\implies a(-2)^2+4=0[/tex]

[tex]\implies 4a=-4[/tex]

[tex]\implies a=-1[/tex]

Therefore, the equation of the parabola in vertex form is:

[tex]y=-(x-6)^2+4[/tex]

Question 12

From inspection of the graph, the vertex is (-5, 0)

[tex]\implies y=a(x+5)^2[/tex]

To find [tex]a[/tex], substitute the coordinates of a point on the curve into the equation.

Using point (-3, 4):

[tex]\implies a(-3+5)^2=4[/tex]

[tex]\implies a(2)^2=4[/tex]

[tex]\implies 4a=4[/tex]

[tex]\implies a=1[/tex]

Therefore, the equation of the parabola in vertex form is:

[tex]y=(x+5)^2[/tex]

We need equation of the parabolas

#1

  • Vertex is at (6,4)

One x intercept is present (4,0)

Now put that in vertex form of parabola

  • y=a(x-h)²+k
  • 0=a(4-6)²+4
  • 4a+4=0
  • a=-1

So

equation

  • y=-(x-6)²+4

#2

  • Vertex at (-5,0)

So equation

  • y=a(x+5)²+0=a(x+5)²

See the general quadratic equation having vertex (0,0) is shifted to (-5,0) means 5 units left .

So there is no a means a=

Equation remains same

  • y=(x+5)²
ACCESS MORE